THE IMPORTANCE OF LAW ENFORCEMENT OF INDONESIA'S TERRITORIAL SEA AREAS AMIDST THE RISE OF TRESPASSING ACTIONS BY FOREIGN PARTIES - Sumartono, Eddy (Pancasila Law Review, 2024)
This research examines the importance of law enforcement in Indonesia's marine territorial area in the face of rampant trespassing by foreign parties. Using a normative juridical qualitative method, this research analyzes the legal framework, policy implementation, and challenges in law enforcement in Indonesia's maritime territory. The results show that Indonesia has a comprehensive legal framework, covering various national laws and ratified international legal instruments. Policy implementation such as the sinking of illegal fishing vessels has shown positive results in reducing violations. However, the main challenges still lie in inter-agency coordination, limited infrastructure, and jurisdictional complexity in border areas. The use of maritime surveillance technology and strengthened international cooperation have improved the effectiveness of law enforcement. The study concludes that a comprehensive approach involving strengthening inter-agency coordination, enhancing law enforcement capacity, investing in surveillance technology, and strengthening international cooperation is needed to address the complex and dynamic challenges of law enforcement in Indonesia's territorial sea.